Reactivity and regioselectivity in Diels–Alder reactions of anion encapsulated fullerenes. Issue 45 (9th November 2017) - Cui, Cheng-Xing; Zhang, Zhao-Pei; Zhu, Lei; Qu, Ling-Bo; Zhang, Yu-Ping; Lan, Yu
Abstract : Theoretical calculations indicate that encapsulated Cl −, Br −, I −, or S 2− are located near the center of the C60 ; however, the encapsulated F − anion is slightly displaced from the center of the cage. Encapsulated N 3− binds with the inner surface of the carbon cage. The opposite regioselectivity of the DA reaction with [N@C60 ] 3− is controlled by the distortion energy of the CPD moiety. Abstract : Encapsulation and surface chemical modification are methodologies to enhance the properties of fullerenes for various applications. Herein, density functional theory calculations are performed to study the Diels–Alder (DA) reactivity of anion encapsulated C60, including [X@C60 ] − (X = F, Cl, Br, or I), [S@C60 ] 2−, and [N@C60 ] 3− . Computational results reveal that encapsulated Cl −, Br −, I −, or S 2− anions are located close to the center of the C60 molecule; however, encapsulated F − is displaced from the center. Encapsulated N 3− bonds to the inner surface of the carbon cage, which leads to a negative charge transfer to the C60 . In [N@C60 ] 3−, C–C bonds near to the encapsulated N atom are more reactive. Our calculations reveal that encapsulated halogen or S anions decrease the DA reactivity because of the stronger closed-shell repulsion of the encapsulated anion. However, encapsulated N 3− increases the DA reactivity. The higher distortion energy of the halogen- or S 2− -anion encapsulated C60 leads to lower reactivity of the 6-5 bond. Opposite regioselectivity of the DA reaction with [N@C60 ] 3− is attributed to distortion energy of the cyclopentadiene (CPD) moiety. The asymmetrical transition state geometry leads to a lower distortion energy of the CPD moiety.